Relationship between mechanical properties in 42SiCr and 42SiMn medium-carbon steels and austempering temperatures - Jeníček, Štěpán; Peković, Michal; Opatová, Kateřina; Vorel, Ivan (Manufacturing Technology Journal, 2021)
In conventional steels, bainitic microstructure which forms under isothermal conditions consists of bainitic ferrite and carbide precipitates whose distribution and size substantially depend on the pa-rameters of isothermal treatment. In CFB steels (Carbide Free Bainite) however, the main micro-structural constituents are bainitic ferrite, retained austenite and, sometimes, the M-A constituent. CFB microstructure may possess better ductility and the same or even higher strength than micro-structures of bainitic ferrite and carbide precipitates. This advantage results from the principle of formation of the CFB microstructure and is related to the absence of brittle carbides and their substi-tution with retained austenite. This paper explores the effect of austempering on mechanical proper-ties of unconventional CFB steels 42SiCr and 42SiMn.
Keywords: Austempering; CFB structure; Silicon; Mechanical properties